Computation of Hilbert sequence for composite quadratic extensions using different type of primes in Q - M. Haghighi; J. Miller (International Journal of Mathematics and Mathematical Sciences)
First, we will give all necessary definitions and theorems. Then the definition of a Hilbert sequence by using a Galois group is introduced. Then by using the Hilbert sequence, we will build tower fields for extension K/k, where K=k(d1,d2) and k=Q for different primes in Q.